Pengaruh Penilaian Kinerja Terhadap Semangat Kerja Studi Pada Karyawan Tetap PT. Aggiomultimex - Amjad Maulana (SMARTINDO, 2023)
This study aims to test the performance appraisal of employee performance. The research method uses a quantitative approach. The sampling technique used is saturated sampling technique. The data collection method uses a questionnaire with a sample of80 permanent employees of PT. Aggiomultimex Sidoarjo. Performance appraisal results have a positive influence on employee performance